A multicenter, randomized, double-blind, placebo-controlled trial evaluating the efficacy and safety of Tong Luo Hua Shi capsule, a modernized Tibetan medicine, in patients with rheumatoid arthritis. Issue 1 (December 2016) - Liu, Wei; Wu, Yuan-Hao; Hu, Si-Yuan; Zhong, Cheng-Liang; Gao, Ming-Li; Liu, Dong-Wu; Wang, Hai-Yun; Chen, Mu-Zhi; Song, Yue-Jin; Yang, Ben-Zha-Xi; Zheng, Qing-Shan; Yao, Hua; et al.
Abstract Background Tong Luo Hua Shi (TLHS) is a new formulation of the traditional Tibetan medicine Wu-wei-gan-lu that has been used for the treatment of rheumatoid arthritis (RA) for hundreds of years in China. This study aimed to evaluate the efficacy and safety of TLHS in patients with RA. Methods This was a randomized, double-blind, placebo-controlled, dose-finding study performed in patients with active RA from five medical centers. Patients received three doses (4.8, 3.6, or 2.4 g/day po) of TLHS or placebo (tid po) for 8 weeks. Blood sampling, physical examination, and assessment of the American College of Rheumatology (ACR) 20 % improvement (ACR20) criteria were performed before and every 2 weeks after starting treatment. The primary endpoint was the ACR20. The secondary endpoints included safety. Results A total of 240 participants were screened and 236 patients were randomized (n = 59/group); 20 dropped out. After 8 weeks, ACR20 improvements in the TLHS 4.8 g and 3.6 g groups were significantly higher than in the placebo group (P < 0.01 andP < 0.05, respectively). ACR50 improvement in the TLHS 4.8 g group was significantly higher compared with the placebo group (P < 0.01). Symptoms of RA were significantly relieved in the TLHS groups. In the TLHS groups, insomnia (n = 1), gastroenteric reactions (n = 2), arrhythmia (n = 1), and minor hepatic lesion (n = 1) were reported; in the placebo group, hepatic dysfunction (n = 1) was reported (P = 0.878). Conclusions TLHS improved the symptoms of patients with RA according to the ACR20. Moreover, TLHS was safe. Trial registration Chinese Clinical Trial Registry:ChiCTR-TRC-12003871 . Registered on 1 January 2012.